Internalisasi Konsep Pendidikan Akhlak Perspektif Buya Hamka dalam Pembelajaran PAI Era Digital - Abdul Afwu Godly Prayitno; Muhammad Yasir Mubarok (Lembaga Sosial Rumah Indonesia, 2022)
Covid-19 outbreak has led to many changes in social life, one of which is education. At present, classes have been replaced by digital media as a space for the development of students' skills and personalities. PAI learning is substantively a subject that emphasizes value cultivation, but we are now facing the problem of the Covid-19 pandemic, which has undermined values. As a result, it is critical to reintroduce disrupted values, particularly through moral education. The great Indonesian cleric, Haji Abdul Malik Karim Amrullah, served as the lens through which the research was conducted. This study uses a qualitative approach with the literature research method. The results of the study show that, from the perspective of Buya Hamka, values or morality are not only limited to students, but also by educators. PAI learning should have an important role in creating an ethical environment. Although technical education can change from offline to online learning, values and substances must be fixed and precise. In the end, values must be transformed into digital communities today through online education, especially through the subject of PAI.